2009
DOI: 10.4049/jimmunol.0900852
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Human Infection with Trypanosoma cruzi Drives CD4+ T Cells to Immune Senescence

Abstract: Previously we found that the frequency of IFN-γ-producing CD8+ T cells specific for Trypanosoma cruzi inversely correlates with disease severity in chronic human Chagas disease along with low levels of IL-2-secreting CD8+ T cells in all clinical stages. This impairment of the parasite-specific T cell responses was associated with phenotypic features of immune senescence of the CD8+ T cell compartment. These data prompted us to address the question of whether the CD4+ T cell compartment also experiences signs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
83
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 47 publications
10
83
1
3
Order By: Relevance
“…In line with this, we have previously shown that the level of HSV-1 latency in CD4 Ϫ/Ϫ mice was significantly higher than that in wt mice (48). Also consistent with our results is the finding that expression of Tim-3 and PD-1 on CD4 ϩ T cells can reduce their function (3,16). Recent studies have now demonstrated that in addition to PD-1, upregulation of Tim-3 (T cell immunoglobulin and mucin domain-containing protein 3) is correlated with T cell exhaustion (23,30,33).…”
Section: Discussionsupporting
confidence: 92%
“…In line with this, we have previously shown that the level of HSV-1 latency in CD4 Ϫ/Ϫ mice was significantly higher than that in wt mice (48). Also consistent with our results is the finding that expression of Tim-3 and PD-1 on CD4 ϩ T cells can reduce their function (3,16). Recent studies have now demonstrated that in addition to PD-1, upregulation of Tim-3 (T cell immunoglobulin and mucin domain-containing protein 3) is correlated with T cell exhaustion (23,30,33).…”
Section: Discussionsupporting
confidence: 92%
“…Studies performed by us and other groups have shown that major T-cell populations, defined by the expression of CD4 and CD8, display phenotypic and functional differences in individuals with different clinical forms of Chagas' disease. To this end, the frequencies of memory cells, as well as senescent cells, have been associated with the chronic cardiac form of Chagas' disease (1,2,23). While these studies have provided critical information, the determination of the contribution of distinct subpopulations to the immunoregulation and functional activities, as well as the antigens that lead to their activation, is critical for the understanding the mechanisms of generation of pathogenic versus protective responses in Chagas' disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is caused by neuronal and cardiomyocyte damage, ultimately resulting in ventricular dilation and subsequent functional heart failure, which can lead to death (44). Cardiac patients display a T-cell-mediated inflammatory response in situ (13,24,41), which is responsible for the pathology; this inflammatory profile is also observed in circulating activated T cells found at high frequencies in these patients (2,16,19,32). Although it is clear that a plethora of parasite and host factors influences the clinical outcome of Chagas' disease, recent studies have suggested that activation of functionally distinct Tcell populations in T. cruzi-infected individuals may be responsible for the establishment of different clinical forms (17,20).…”
mentioning
confidence: 99%
“…ϩ T cell exhaustion, while currently less widely studied, appears to be no less prevalent, as it has already been implicated in chronic Trypanosoma cruzi, CMV, and HIV infections (1,10,12). More recently, CD4 ϩ Tim-3 ϩ T cells were implicated in primary HSV-1 infection, and by altering the interaction of Tim-3 with its ligand, the authors could produce therapeutic effects on ocular lesions (51,52).…”
Section: Discussionmentioning
confidence: 99%